100k views
1 vote
If fx) = 2x2 + 3x and g(x) = x - 2, what is (f+ g)(2)?

ОА. 16
ов. 14
Ос. 12
OD. 10
ОЕ. 8

User Alicja
by
4.2k points

1 Answer

5 votes

Explanation:


f(x) = 2 {x}^(2) + 3x \\ \\ g(x) = x - 2 \\ \\ \therefore \: (f + g)(x) = f(x) + g(x) \\ = 2 {x}^(2) + 3x + x - 2 \\ \therefore \: (f + g)(x) = 2 {x}^(2) + 4x - 2 \\ \\ \therefore \: (f + g)(2) = 2 * {2}^(2) + 4 * 2 - 2 \\ = 8 + 8 - 2 \\ \huge \red{ \boxed{\therefore \: (f + g)(2)= 14 }}\\

Hence, option B 14 is the correct answer.

User Vmanjz
by
4.5k points